New Modeling Approaches for Ethylene Oxychlorination in Fluidized Bed Reactors: Industrial and Low Flow Rate Conditions - El Bazi, Wail; Bideq, Mustapha; El-Abidi, Abderrahim; Yadir, Said (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
A simple model (Continuous Stirred-Tank Reactor) has been developed to predict the behavior of industrial ethylene oxychlorination fluidized beds operating in a turbulent regime. The approach showed good agreement both with results from industrial reactors and with those corresponding to the (Simple two phases-Plug bubble-Mixed flow emulsion approach) validated in the literature. For low flow rates, the use of the (Simple two phases - Plug bubble - Plug emulsion model) adapted to these conditions enabled us to highlight the location and extent of undesirable thermal hot spots for the process, and to propose actions to control them by acting on the temperature and/or on the feed gas flows. By comparing this model with the plug approach, the significant slowdown in ethylene conversion caused by resistance to mass transfer when feed flow rates are low is highlighted. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).